2003
DOI: 10.1034/j.1399-3011.2003.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 1‐aminocyclohexane‐1‐carboxylic acid in position 2 or 3 of AVP and its analogues on their pharmacological properties

Abstract: In this study we describe the synthesis and some pharmacological properties of seven new analogues of arginine vasopressin (AVP) substituted in position 2 or 3 with 1-aminocyclohexane-1-carboxylic acid (Acc). All peptides were tested for the pressor, antidiuretic and uterotonic in vitro activities. The Acc3 modifications of AVP, dAVP, [d-Arg8]VP and [Cpa1]AVP have been found to be deleterious for interaction with all three neurohypophyseal hormone receptors, as judged from the several orders of magnitude decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 27 publications
4
30
0
Order By: Relevance
“…We demonstrated that the arginine vasopressin analogues modified at position 2 with either L or D b-(1-naphthyl)-alanine were moderately potent and selective oxytocin antagonists in vitro [22], while [D-Arg 8 ]VP substituted at position 3 with b-(2-naphthyl)-alanine turned out to be a potent and selective antagonist of the pressor response to AVP [23]. We have also shown that introduction of either 1-aminocyclohexane-1-carboxylic acid (Acc, also known as Ac 6 c) or 1-aminocyclopentane-1-carboxylic acid (Apc, also known as Ac 5 c) into position 2 of AVP and some of its analogues resulted in compounds having high antidiuretic potency, low and graded pressor activity, and either no activity or low oxytocin antagonizing activity in the uterotonic in vitro tests [24][25][26]. Recently, we described some pharmacological activities of three analogues having bulky 3,3-diphenyl-L-alanine (Dip) in position 2 [27].…”
Section: Introductionmentioning
confidence: 93%
“…We demonstrated that the arginine vasopressin analogues modified at position 2 with either L or D b-(1-naphthyl)-alanine were moderately potent and selective oxytocin antagonists in vitro [22], while [D-Arg 8 ]VP substituted at position 3 with b-(2-naphthyl)-alanine turned out to be a potent and selective antagonist of the pressor response to AVP [23]. We have also shown that introduction of either 1-aminocyclohexane-1-carboxylic acid (Acc, also known as Ac 6 c) or 1-aminocyclopentane-1-carboxylic acid (Apc, also known as Ac 5 c) into position 2 of AVP and some of its analogues resulted in compounds having high antidiuretic potency, low and graded pressor activity, and either no activity or low oxytocin antagonizing activity in the uterotonic in vitro tests [24][25][26]. Recently, we described some pharmacological activities of three analogues having bulky 3,3-diphenyl-L-alanine (Dip) in position 2 [27].…”
Section: Introductionmentioning
confidence: 93%
“…Vasopressin analogues were synthesized according to the literature. 16 The purity and identity of each peptide was determined by high performance liquid chromatography (HPLC) and fat atom bombardment (FAB) mass spectrometry. The products were purified by HPLC partition chromatography using two solvent systems: 0.1% aqueous trifluoroacetic acid (TFA) and acetonitrile:0.1 TFA (80:20 v/v), followed by Sephadex G-15 and LH-20 gel filtration.…”
Section: Experimental Peptide Samplesmentioning
confidence: 99%
“…This analogue also displays weak antiuterotonic and antipressor properties 16 In another analogue, Phe at position 3 was replaced with Acc. This modification caused the loss of agonism towards the OT receptors.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, there is evident relationship between the value of valence angle between the aromatic rings in positions 2 and 3 of in the receptor-bound conformation of the analog and its biological activity. Identical deleterious effect of substitution in position 3 on the biological activity has been earlier observed for vasopressin analogs substituted with 1-aminocyclohexanecarboxylic acid (Acc) [14]. To exclude the possibility, that the value of Aic-Ar valence angle might depend on the residues sequence (i.e.…”
Section: Relationship Between the Biological Activity Of The Analogs mentioning
confidence: 96%
“…To better understanding the role of the residues in positions 2 and 3 of AVP molecule, several studies, both experimental and theoretical have been undertaken [13 -20]. It has been shown that modifications of positions 2 and 3 alone or in combination with other suitable changes, yield analogs with attractive pharmacological properties [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%